Energy saving and user satisfaction for a new advanced public lighting system. (1st September 2019) - Beccali, M.; Bonomolo, M.; Lo Brano, V.; Ciulla, G.; Di Dio, V.; Massaro, F.; Favuzza, S.
Highlights: The retrofit of urban lighting systems is a means of improving their performance. An original method for structuring the design process is presented. A pilot installation has been realised and monitored to test pre-design assumptions. The test installation has also been used to conduct a survey about user satisfaction. Final design will ensure user satisfaction, energy saving and economic features. Abstract: The retrofit of urban lighting systems is often an advantageous means of achieving notable energy savings and improvements in the quality of light. User habits, expectations and lifestyle can contribute to the design of these systems, for example in deciding on the most appropriate control strategies or the light quality. The influence of such variables can be extended to the overall system performance. This paper presents a method of street lighting design based on two kinds of analysis carried out in a defined test area: measurements (by means of a monitoring study) and user preferences (by means of a survey). The results of this data analysis create the basis for the final design step. The proposed method is applied in a case study: the lighting system of the outdoor areas of the University of Palermo campus (Italy). The results show that the proposed method can be used to optimise the performance of a lighting plant in terms of energy saving and quality of light, while also taking into account the opinions of local users. Indeed, the results of the survey show that 81% of the users feel safe in test areas, 80% declare very good satisfaction with the project, and the totality of the sample would like the implementation of new features embedded in the lighting infrastructure. Expected results of energy savings in the entire campus will be about 70% with a short investment return time (3–4 years).